Executing large-scale processesin a blockchain - Mahalingam Ramkumar (Journal of Capital Markets Studies (JCMS), 2018)
Purpose - The purpose of this paper is to examine the blockchain as a trusted computing platform. Understanding the strengths and limitations of this platform is essential to execute large-scale real-world applications in blockchains. Design/methodology/approach - This paper proposes several modifications to conventional blockchain networks to improve the scale and scope of applications. Findings - Simple modifications to cryptographic protocols for constructing blockchain ledgers, and digital signatures for authentication of transactions, are sufficient to realize a scalable blockchain platform. Originality/value - The original contributions of this paper are concrete steps to overcome limitations of current blockchain networks.
Keywords: 330; Cryptography; Blockchain; Scalability; Transactions; Blockchain networks